Seismic Strengthening of Soft-Story RC Moment Frames - Wararuksajja, Wongsa; Leelataviwat, Sutat; Warnitchai, Pennung; Bing, Li; Tariq, Hasan; Naiyana, Nattakan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
This study was conducted to compare seismic strengthening techniques for soft-story RC buildings and to retrofit actual buildings as a pilot case. Two methods were selected, a strengthening technique using Buckling Restrained Braces (BRBs) and a conventional method using concrete column jacketing. Two soft-story RC buildings located in northern Thailand having the same structural framing and details were strengthened using the two different approaches. Background works that formed the basis for the strengthening design concepts of these buildings are briefly presented. Nonlinear analyses are used to assess the performance of the two buildings and to compare their response with that of the un-retrofitted structure. The effectiveness of using passive energy dissipating devices such as BRBs in controlling the excessive soft story drift is discussed in comparison with that of using the concrete jacketing method. The differences and limitations of the two strengthening techniques are also discussed.